Lymphoplasmacytic Meningoencephalitis and Neuronal Necrosis Associated With Parvoviral Infection in Cats. Issue 4 (July 2019) - Kokosinska, Anna; Maboni, Grazieli; Kelly, Kathleen M.; Molesan, Alex; Sanchez, Susan; Saliki, Jeremiah T.; Rissi, Daniel R.
Neurologic manifestations other than cerebellar hypoplasia are rarely associated with feline panleukopenia virus (FPV) infection in cats. Here the authors describe lymphoplasmacytic meningoencephalitis and neuronal necrosis in 2 cats autopsied after exhibiting ataxia and nystagmus. Gross changes consisted of cerebellar herniation through the foramen magnum, with flattening of cerebrocortical gyri and narrowing of sulci. Histologically, lymphoplasmacytic meningoencephalitis, extensive neuronal necrosis, and neuroaxonal degeneration with digestion chambers were present in the telencephalon and brain stem in both cats. Frozen brain tissue of both cats was positive for parvoviral antigen via fluorescent antibody testing, and formalin-fixed, paraffin-embedded tissue sections of brain were immunoreactive for parvovirus antigen and positive for parvoviral DNA on in situ hybridization. Frozen brain tissue from 1 case was positive for parvovirus NS1 and VP2 genes using conventional polymerase chain reaction, and subsequent DNA sequencing and phylogenetic analysis revealed that the viral strain was a FPV. Reverse transcription quantitative polymerase chain reaction on formalin-fixed, paraffin-embedded brain tissue revealed high levels of parvovirus in both cases, supporting an acute and active viral infection. Although rare, FPV infection should be considered in cases of lymphoplasmacytic meningoencephalitis and neuronal necrosis in cats.